Model Motivasi Trisula: Sintesis Baru Teori Motivasi Berprestasi - Purwanto, Edy (Jurnal Psikologi, 2014)
The purpose of this study was to find out a comprehensive model of achievement motivation appropriate for Indonesian students. Specifically, this study examined the contribution of task-value, self-efficacy and goal orientation in influencing students’ achievement motivation. The subjects of this research were 393 high school students, 219 of them are female and 174 are male. 46% of them were senior high school and 54% junior, high school students. 45% were from public schools and 55% from religion-based private schools. The task-value, self-efficacy, goal orientation and achievement motivation as scaling instruments used in this study were developed from Motivated Strategies for Learning Questionnaire Manual. The instruments had been tested and proved valid and reliable. Analysis of model testing data was done using technique of confirmatory factor analysis. The results showed that the trisula model of achievement motivation was reliable. The task-value, self-efficacy and goal orientation are significant loading factors for achievement motivation. The self-efficacy also is a significant loading factor for the task-value and goal orientation. Keywords: achievement motivation, goal orientation, self-efficacy, task-value